(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research paper presents the development of a novel bidirectional dc/dc converter (BDC) that has been patented. The converter is meant to connect a primary energy storage (ES1), a secondary energy storage (ES2), and a dc-bus with varying voltage levels. The intended application of this converter is in hybrid electric vehicle systems. The converter under consideration has the capability to function in two distinct modes: step-up mode, also known as low-voltage dual-source-powering mode, and step- down mode, often referred to as high-voltage dc-link energy-regenerating mode. In both of these modes, the converter is equipped with bidirectional power flow regulation. Furthermore, the model possesses the capability to autonomously regulate the distribution of power between two low-voltage sources, namely in the low-voltage dual-source buck/boost mode. In this discussion, we will examine the circuit setup, operation, steady-state analysis, and closed-loop management of the proposed BDC (Brushless DC) system, focusing on its three modes of power transfer. Additionally, the findings of both computational and experimental tests conducted on a 1 kW prototype system are presented in order to verify the efficacy of the suggested converter.